Open-access mega-journals: The future of scholarly communication or academic dumping ground? A review. Issue 2 (13th March 2017) - Spezi, Valerie; Wakeling, Simon; Pinfield, Stephen; Creaser, Claire; Fry, Jenny; Willett, Peter
Abstract : Purpose: Open-access mega-journals (OAMJs) represent an increasingly important part of the scholarly communication landscape. OAMJs, such as PLOS ONE, are large scale, broad scope journals that operate an open access business model (normally based on article-processing charges), and which employ a novel form of peer review, focussing on scientific "soundness" and eschewing judgement of novelty or importance. The purpose of this paper is to examine the discourses relating to OAMJs, and their place within scholarly publishing, and considers attitudes towards mega-journals within the academic community. Design/methodology/approach: This paper presents a review of the literature of OAMJs structured around four defining characteristics: scale, disciplinary scope, peer review policy, and economic model. The existing scholarly literature was augmented by searches of more informal outputs, such as blogs and e-mail discussion lists, to capture the debate in its entirety. Findings: While the academic literature relating specifically to OAMJs is relatively sparse, discussion in other fora is detailed and animated, with debates ranging from the sustainability and ethics of the mega-journal model, to the impact of soundness-only peer review on article quality and discoverability, and the potential for OAMJs to represent a paradigm-shifting development in scholarly publishing. Originality/value: This paper represents the first comprehensive review of the mega-journal phenomenon, drawing not only on the published academic literature, but also grey, professional and informal sources. The paper advances a number of ways in which the role of OAMJs in the scholarly communication environment can be conceptualised.